(untitled) (Pulse, 2014)
Transfusion transmitted infection (TTIs) is still a concern associated with blood transfusion as hepatitis B and hepatitis C remains a major public health problem in a country like Bangladesh. The trends of the prevalence of HBsAg and HCV infection among the healthy blood donors even in a tertiary level hospital could be a guide for planning and implementing programs for preventive measures. All samples of a total 18,381 unit of blood were screened for hepatitis B surface antigen and anti-hepatitis C virus antibodies at Apollo Hospitals Dhaka over a period of 5 years (2007-2011). The prevalence of HBV and HCV infection was calculated by year to demonstrate the trends. The overall sero prevalence rate of HBV and HCV among all blood donors at Apollo Hospitals, Dhaka during 2007 to 2011 was 1.42% and 0.10% respectively. There was decreasing trend observed in sero prevalence of HBV (1.77% vs 1.64%) and HCV (0.13% vs 0.02%) over five years of time, although this change was not statistically significant (p=0.16 for HBV and p=0.20 for HCV). However, a significant decreasing trend was observed in the sero prevalence of HBV among blood donors aged 30 years and above, which was 1.04% in 2011 against 1.73% in 2007 (p=0.04). The decreasing trend in the prevalence of HBV and HCV infection might be the result of improvement in donor recruitment and selection, replacement donation exclusion in transfusion services, and possibly decreasing HBV infection prevalence in general population. DOI: http://dx.doi.org/10.3329/pulse.v6i1-2.20330 Pulse Vol.6 January-December 2013 p.27-32